Effect of Partial Rootzone Drying (PRD) on growth, Water Use Efficiency (WUE) and yield of tomatoes grown in soilless culture - Ali, Hassan Ibrahim; Ismail, Mohd Razi; Mohd Saud, Halimi; Manan, Mohd Mokhtaruddin (Universiti Putra Malaysia Press, 2004)
An investigation was carried out at the Department of Crop Science, Universiti Putra Malaysia (UPM) to examine the effect of PRD using soilless media, a mixture of 70% coconut coir dust and peat (3:2 respectively) amended with 30% rice straw compost. Tomato (Lycopersicon esculentum Mill cv Red Rock) plants were exposed to two different water treatments, which was either well-watered (control) or partially irrigated on half of the roots (PRD). Reduction in water availability in the media with PRD treatment caused a significant decrease in leaf expansion, leaf area and stomatal conductance. Proline was significantly increase with PRD. There was no significant reduction in dry matter partitioning and yield between well-watered and PRD-treated plants. Water use efficiency also was significantly increased with PRD.